2014
DOI: 10.1117/1.jbo.19.1.016015
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of high-frequency ultrasonic transducer design for laser-scanning photoacoustic ophthalmoscopy

Abstract: Abstract. Photoacoustic ophthalmoscopy (PAOM) is a high-resolution in vivo imaging modality that is capable of providing specific optical absorption information for the retina. A high-frequency ultrasonic transducer is one of the key components in PAOM, which is in contact with the eyelid through coupling gel during imaging. The ultrasonic transducer plays a crucial role in determining the image quality affected by parameters such as spatial resolution, signal-to-noise ratio, and field of view. In this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The general fabrication process previously reported was modified to fabricate the four-layered IVUS transducer 23 . The IVUS transducer was then inserted into customized probe housing (a stainless steel tube one window; OD: 1 mm; length: 2 mm).…”
Section: Methodsmentioning
confidence: 99%
“…The general fabrication process previously reported was modified to fabricate the four-layered IVUS transducer 23 . The IVUS transducer was then inserted into customized probe housing (a stainless steel tube one window; OD: 1 mm; length: 2 mm).…”
Section: Methodsmentioning
confidence: 99%
“…However, a transducer with large bandwidth needs to be carefully chosen. Due to ocular attenuation of high frequency ultrasonic waves, it’s suggested that high sensitivity in PAOM is more achievable with relative narrow bandwidth [116] . Therefore, the tradeoff between axial resolution and detection sensitivity needs a balance.…”
Section: Future Studies To Bring Photoacoustic Imaging To the Clinicamentioning
confidence: 99%
“…[1][2][3][4][5][6] However, conventional manufacturing processes such as etching and dicing for piezoelectric ceramics fabrication have limited capability of achieving complex geometry and high resolution(X-Y resolution<25ÎŒm). Moreover, mechanical stress caused by the traditional machining processes can result in grain pullout, strength degradation and depolarization of the near surface region, which will led to significant degradation in piezoelectric device performance.…”
Section: Introductionmentioning
confidence: 99%